The Cute : Documents of Contemporary Art - Ngai, Sianne (London ; Cambridge, Massachusetts : Whitechapel Gallery : The MIT Press, 2022)
Blake, Nayland ; Chan, Paul ; Darger, Henry ; Howells, Adrian ; Huxtable, Juliana ; Johnson, Larry ; Kelley, Mike ; Kenning, Dean ; Koons, Jeff ; Lewis, Wyndham ; Madani, Tala ; Mammalian Diving Reflex ; Messager, Annette ; Mori, Mariko ; Nara, Yoshitomo ; Charlemagne Palestine ; Rottenberg, Mika ; Ruppersberg, Allen ; Schneemann, Carolee ; Smith, Jack ; Walker, Kara ; Warhol, Andy
boek